Gambaran Pengetahuan Masyarakat Tentang Vaksinasi Covid-19 - Mardiati Barus; Pomarida Simbolon; Ertika Sari Uli Panjaitan (STIKES Citra Delima Bangka Belitung, 2023)
Covid-19 is an infectious disease designated as a global health problem which as subsequently designated as a pandemic by the World Health Organization. Starting in 2021, Covid-19 vaccinations have begun to be carried out in various countries, including Indonesia. Lack of public knowledge causes one of the factors that the implementation of vaccination is not optimal. One of the people's refusal is not to get vaccinated because people do not know the purpose of the vaccination. The purpose of this study is to identify the level of public knowledge about Covid-19 vaccination at Lumban Pinasa Village, Habinsaran District. The population in the study amount to 400 people, the sampling technique used the Slovin formula obtained as many as 80 people. This research use descriptive research method with the sampling technique is random sampling. The level of public knowledge about Covid-19 vaccination has good knowledge of 73 respondents (91.3%), and sufficient knowledge of 7 people (8.8%). It is hoped that the public will maintain knowledge about Covid-19 vaccination and continue to seek information related to Covid-19 vaccination.